Psychiatric diseases: Need for an increased awareness among the anesthesiologists - Sukhminder Jit Singh Bajwa; Ravi Jindal; Jasbir Kaur; Amarjit Singh (Wolters Kluwer Medknow Publications, 2011)
Psychological disorders and psychiatric diseases have been on the rise since the last three decades. An increasing number of such patients are encountered nowadays for elective or emergency surgery. A multi-array of challenges are faced while anesthetizing these patients or treating them in an intensive care unit. The problems include the deteriorated mental physiology, altered cognition and the possible drug interactions with psychotropic medications. The challenge starts from the preoperative assessment stage. Knowledge of the pharmacological profile of the various anti-psychotic drugs, their side-effects and drug interactions are of prime importance for an anesthesiologist to facilitate smooth delivery of anesthesia in such patients. It is important to formulate a clear plan to deal with any challenge in the perioperative or postoperative period. All the clinical aspects and various definitions of mental disorders in the present article have been used as per the fourth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV). We reviewed the advances in psychiatric diseases, their treatment and their implications on delivery of anesthesia.